Efficacy of Different Concentrations of NAA on Selected Ornamental Woody Shrubs Cuttings - Endre Kentelky (MDPI AG, 2021)
Ornamental woody shrubs are used in landscape design worldwide. Their propagation can be made generatively and vegetatively. Vegetative propagation methods are mostly used by nurseries, as such methods are quick and the newly propagated plants inherit the genetics of the mother plant. However, rooting in some woody plants is slow and, unfortunately, sometimes produces only a small number of rooted cuttings. In this study, shoot cuttings from six selected ornamental woody shrubs were subjected to different concentrations of rooting stimulators (0.5 (NAA5) and 0.8 (NAA8) % concentrations of 1-Naphthylacetic acid; cuttings without treatment were considered as control) and propagated in two different periods (spring and summer). Our results show that significant changes were obtained in the plants under the different treatments. Most of the plants showed a positive response to both treatments, expect for Cotinus coggygria ‘Royal Purple’, which, compared to control, registered decreases in all the tested parameters under NAA5 treatment. Ilex aquifolium was the species that showed increments in all the parameters when NAA treatments were applied. In conclusion, our research suggests that NAA increases rooting in ornamental woody shrubs, although in some cases rooting could be a species-dependent process.